Copulae in the Arabic Noun Phrase : a Unified Analysis of Arabic Adnominal Markers. - Grande, Francesco (Studies in Semitic languages and linguistics, 2013)
Morphemes combined with the Arabic noun exhibit many puzzling properties, still unaccounted for in the literature. This book proposes a new, unified explanation, analyzing these morphemes as copulae, with the constructions in which they occur as instances of predication.